Housing affordability in the state of Selangor, Malaysia - Mohamed Osman, Mariana; Khalid, Najihan; Muhammad Yusop, Siti Wahidah (American Scientific Publishers, 2017)
This paper examines the issue of housing affordability in the most developed state in Malaysia namely Selangor, looking within the context of housing as a need to every individual and increasing the quality of housing will improve peoples’ quality of life. In Malaysia, housing policies have focused primarily on demand side and this has led to unregulated housing supply and prices. The study examines housing affordability with the view of housing for the low income group or bottom 40 percent of the population is necessary, thus improving the affordability of housing in general. Five perspectives are discussed, namely definition and measurement of affordability, household income, housing prices, affordable housing policy in Selangor; and econometric analysis of housing affordability. The paper analysed the housing affordability index (HAI) for the year 2014 in all nine districts in the state of Selangor using the median income over the overall median housing prices. From the analysis, it was found that the median all house prices for the state of Selangor was at RM300,000 with median annual income at RM74,568.00 making the affordability level is at 4.0, which is considered to be moderately unaffordable. Futhermore, the study identified more than 50% of the household in Selangor have an average monthly income of around RM6,214 making their affordable housing price, based on housing affordability index of 3, should be below RM220,000. The study found that locational factors, types of economic based of the areas and the income level of population influence the calculated index making the affordability level differ between districts. In certain districts, monitoring and control from the related authorities on the construction of affordable houses are essential in ensuring the continued supply of these houses to the targeted low income population within the community.